The Role of Kelompok Informasi Masyarakat (KIM) in Developing Public Information Literacy in Pandeglang Regency - Annisarizki Annisarizki; Siska Mardiana (Future Science, 2022)
The establishment of KelompokInformasiMasyarakat (KIM) in Pandeglang Regency by the Pandeglang Regency Communication, Code and Statistics Office is expected to be a mouthpiece between the Pandeglang Regency Government and disadvantaged rural communities in developing information literacy. Through a qualitative approach with descriptive research methods, this study focuses on the role of KIM in developing information literacy in underdeveloped villages. This study seeks to find out the role of KIM in conducting information literacy about the Pandeglang Regency government program. The results of the study show the role of KIM in developing information literacy for the people of Pandeglang Regency, collecting, informing and managing information about programs that are being and will be run by the Pandeglang Regency government in 16 underdeveloped villages that are still difficult to access the internet, such as educating about COVID-19, conducting program socialization